Microspore Induced Doubled Haploids Production from Ethyl Methanesulfonate (EMS) Soaked Flower Buds Is an Efficient Strategy for Mutagenesis in Chinese Cabbage - Lu, Yin; Dai, Shuangyan; Gu, Aixia; Liu, Mengyang; Wang, Yanhua; Luo, Shuangxia; Zhao, Yujing; Wang, Shan; Xuan, Shuxin; Chen, Xueping; Li, Xiaofeng; Bonnema, Guusje; et al. (Frontiers in Plant Science, 2016)
Chinese cabbage buds were soaked with Ethyl methanesulfonate (EMS) was used to soak to induce mutagenesis. The influence of different EMS concentrations and treatment durations on microspore development, embryo production rate and seedling rate were evaluated in five genotypes of Chinese cabbage genotypes. Mutations in four color-related genes were identified using hHigh resolution melting (HRM) curves of their PCR products. was used to identify mutations in four color-related genes. The results demonstrated that an EMS concentration greater than 0.1% was lethal to microspores. The greatest embryo production and seedling rates were observed when buds were treated with 0.03 to 0.1% EMS for 5 to 10 min, while EMS concentrations greater than 0.1% were lethal to the microspores.. These conditions also facilitated culturing of microspores. In total, 142 mutants with distinct variations in leaf shape, leaf color, corolla size, flower color, bolting time and downy mildew resistance were identified from 475 microspore culture derived Doubled Haploids plantlets. Our results suggest demonstrate that microspore derived Doubled Haploids from soaking of buds with EMS soaked buds is anrepresents an efficient approach to the rapidly generation generate of Chinese cabbage mutants.